TINDAKAN RUSIA MEMBERIKAN SUAKA POLITIK KEPADA MANTAN PRESIDEN UKRAINA VIKTOR YANUKOVYCH TAHUN 2014 - Febriono, Tri Agung; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to understand why Russia granted political asylum to ousted Ukrainian President Viktor Yanukovych on February 2014. In fact, from the perspective of international law on political asylum, Viktor Yanukovych shouldnât be able to get asylum everywhere because he is an international political criminals and fugitives on chages of mass murder during the crisis that occured in Ukraine after he rejected cooperation agreement with Europe Union (EU). Viktor Yanukovych was supposed to guaranteed the punishment that has been alleged.This research has built by using neorealism perspective of international relations and supported by securitization theories and international law about legalitation theories. This research also using international system as the level of analyze which on Russia granted asylum to Viktor Yanukovych. Formulation of all argument, facts, and theoretical framework in this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the jounals, books, research paper, news article, official publication, conference papers, and then from internet pages that has related in this case research.This research has formulated answer-hypothesis that reason Russia granted political asylum to Viktor Yanukovych because Viktor Yanukovych has a closenees with Russia and any gaps on international law governing political asylum.Keywords: Viktor Yanukovych, Ukraine crisis, political asylum, Russian response